Strategies of minimization of Sammon’s mapping error - Dzemyda, Gintautas; Bernatavičienė, Jolita; Kurasova, Olga; Marcinkevičius, Virginijus (Lietuvos matematikos rinkinys, 2004)
The classic algorithm for Sammon’s projection and two new its modifications are examined in details. All the algorithms are oriented to minimize the projection error. The discovered new ways for minimization of the projection error makes a background for the further research in this field.